(untitled) (The Strategic Review for Southern Africa, 2022)
Growing international concern over Russia’s military and political resurgence in Africa and the possibility of creating a renewed Cold War has been rekindled by Russia’s invasion of Ukraine and the outbreak of war in Europe in February 2022. Russia’s growing influence in Africa through the re-establishment of old ties and the creation of new ones has been perceived as a quest to re-establish the geopolitical gains that the Soviet Union achieved before its collapse in 1989. Increasing demand for Russian weaponry and equipment, support for unpopular, illegitimate, or unconstitutionally elected leaders, and the targeting and interest in mining concessions and natural resources are considered by the West to be a threat to democratic gains and stability in an already fragile continent. Several questions arise as a result of the deepfake propaganda around occurrences on the continent. How has Russia’s resurgence or reemergence manifested on the African continent? What instruments does Russia utilise to exert its influence in Africa? What are the potential opportunities and threats of Russian presence in West Africa and the Sahel? And how will other global actors be affected? This debate article seeks to examine a particular aspect of Russia’s resurgence on the African continent, namely, the presence of Russian proxies in West Africa and the Sahel. It examines the multiple dynamics created by their presence, the potential threats that their proliferation and activities generate in an already fragile sub-region, and how such activities, if unconstrained, can impose other potential dangers on the continent and the globe.